Pancreatic Neuroendocrine Tumors: Entering a New Era - Oberstein, Paul E; Remotti, Helen; Saif, Muhammad Wasif; Libutti, Steven K (JOP. Journal of the Pancreas, 2012)
Neuroendocrine tumors (NETs) describe a heterogeneous group of tumors with a wide range of morphologic, functional, and behavioral characteristics. These tumors are generally slow growing and behave in an indolent fashion. However, they have the potential to spread, primarily to the liver and when they do, they can be life threatening and difficult to treat with current modalities. A subset of NETs, the pancreatic neuroendocrine tumors (pNET) represent a small percentage of all pancreatic tumors (1.3%) but their incidence is rising. Prior to 2011, the only approved agent for unresectable pNETs was streptozocin (often used in combination with doxorubicin) but the efficacy of this drug was questionable. In 2011, the landscape of treatment for pNET was changed with the approval of the first new agents in 20 years, sunitinib and everolimus, that demonstrated improvement in time to progression in patients with progressive pNET. Sunitinib is a multikinase inhibitor and everolimus is an inhibitor of the mammalian target of rapamycin (mTOR) pathway. These drugs were approved by the Food and Drug Administration (FDA) on the basis of separate large randomized placebo-controlled trials. Data from these two trials and an additional phase III trial looking at everolimus in other neuroendocrine tumors has generated intense interest in this challenging disease. At the 2012 American Society of Clinical Oncology (ASCO) Gastrointestinal Cancers Symposium, several researchers presented updated data regarding the risk stratification, treatment, and outcome for patients with pNET in the new era of targeted therapy. Choti et al. (Abstract #187) reviewed demographic data from a large set of patients who presented to National Comprehensive Cancer Network (NCCN) sites with neuroendocrine tumors. Casciano et al. (Abstract #226) and Signorovitch et al. (Abstract #237) presented post-approval analysis of the relative role of everolimus and sunitinib in the treatment of pNET. Alistar et al. (Abstract #166) explored predictive biomarkers in pNET, and Yao et al. (Abstract #157) conducted multivariate analysis of patients treated with everolimus in the phase III, RADIANT-2 trial which included the identification of relevant biomarkers. Hobday et al. (Abstract #260) and Bergsland et al. (Abstract #285) reported phase II data from two clinical trials looking at novel targeted combinations for the treatment of pNET. Finally the role of treatment for poorly differentiated NETs (including pNETs) remains ill-defined and Yamaguchi et al. (Abstract #274) presented a report reviewing the experience at 23 centers in Japan in treating this population. The authors review and summarize these abstracts in this article.